2012
DOI: 10.1186/1471-2474-13-234
|View full text |Cite
|
Sign up to set email alerts
|

The PRESLO study: evaluation of a global secondary low back pain prevention program for health care personnel in a hospital setting. Multicenter, randomized intervention trial

Abstract: BackgroundCommon low back pain represents a major public health problem in terms of its direct cost to health care and its socio-economic repercussions. Ten percent of individuals who suffer from low back pain evolve toward a chronic case and as such are responsible for 75 to 80% of the direct cost of low back pain. It is therefore imperative to highlight the predictive factors of low back pain chronification in order to lighten the economic burden of low back pain-related invalidity. Despite being particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This study also found that among nurses with a history of low back pain, those who had attended prevention training had a higher ability to prevent occupational low back pain than those who had not. Like Denis et al ( 48 ) opinion, this finding indicated that targeted training is positive for nurses with recurrence and chronicity risk of occupational low back pain. Low back pain often recurs among nurses ( 5 ).…”
Section: Discussionsupporting
confidence: 56%
“…This study also found that among nurses with a history of low back pain, those who had attended prevention training had a higher ability to prevent occupational low back pain than those who had not. Like Denis et al ( 48 ) opinion, this finding indicated that targeted training is positive for nurses with recurrence and chronicity risk of occupational low back pain. Low back pain often recurs among nurses ( 5 ).…”
Section: Discussionsupporting
confidence: 56%
“…The relevant authorities (Ethics Committee, DirectorateGeneral for Health and Consumers, National Commission for Data Protection and Liberties -CNIL France) approved the study, which was authorized by the direction of the Hospices Civils de Lyon, and the Committees for Health, Safety and Working Conditions (CHSCT) of each participating hospital. The study was registered in ClinicalTrials.gov (NCT00782925) and its protocol has been published elsewhere (18).…”
Section: Methodsmentioning
confidence: 99%
“…The exercise therapy program comprised three steps (18). First, a 2-hour education session was delivered to the participants about LBP, pain pathways, fear-avoidance beliefs and coping.…”
Section: Interventionmentioning
confidence: 99%
“…Low back pain (LBP) has a high prevalence and incidence in Switzerland [ 1 ] and Germany [ 2 ] with estimates suggesting a 4 week prevalence of 43% among the Swiss population in 2007 [ 3 ]. Of all back pain patients with acute problems, 6 to 17% are sliding into chronicity [ 4 ] [ 5 ]. These problems frequently lead to a reduction in patients’ quality of life and working ability.…”
Section: Introductionmentioning
confidence: 99%